(untitled) (Texas Journal of Philology, Culture and History, 2023)
The article deals with questions about how the language forms of kinship terms changed from the point of view of national ethnogenesis, how the terms of kinship changed with the development of social and family relations, their phonetic, nominal and semantic similarity.